Extrinsic origins of the somatostatin and neuropeptide Y innervation of the rat basolateral amygdala. (21st May 2015) - McDonald, A.J.; Zaric, V.
Highlights: 2% of cells in the entorhinal cortex that project to the BLC contain somatostatin (SOM). Some of these nonpyramidal neurons also express NPY and GABA. None of these neurons nonpyramidal neurons express parvalbumin or VIP. SOM+/NPY+ neurons projecting to the BLC are also seen in other amygdalar nuclei. No neurons in the prefrontal cortex that project to the BLC contain SOM, NPY or GABA. Abstract: The amygdalar basolateral nuclear complex (BLC) is a cortex-like structure that receives inputs from many cortical areas. It has long been assumed that cortico-amygdalar projections, as well as inter-areal intracortical connections, arise from cortical pyramidal cells. However, recent studies have shown that GABAergic long-range nonpyramidal neurons (LRNP neurons) in the cortex also contribute to inter-areal connections. The present study combined Fluorogold (FG) retrograde tract tracing with immunohistochemistry for cortical nonpyramidal neuronal markers to determine if cortical LRNP neurons project to the BLC in the rat. Injections of FG into the BLC produced widespread retrograde labeling in the cerebral hemispheres and diencephalon. Triple-labeling for FG, somatostatin (SOM), and neuropeptide Y (NPY) revealed a small number of FG+/SOM+/NPY+ neurons and FG+/SOM+/NPY− neurons in the lateral entorhinal area, amygdalopiriform transition area, and piriform cortex, but not in the prefrontal and insular cortices, or in the diencephalon. In addition, FG+/SOM+/NPY+ neurons were observed in the amygdalostriatal transition area and in a zone surrounding the intercalated nuclei. About half of the SOM+ neurons in the lateral entorhinal area labeled by FG were GABA+. FG+ neurons containing parvalbumin were only seen in the basal forebrain, and no FG+ neurons containing vasoactive intestinal peptide were observed in any brain region. Since LRNP neurons involved in corticocortical connections are critical for synchronous oscillations that allow temporal coordination between distant cortical regions, the LRNP neurons identified in this study may play a role in the synchronous oscillations of the BLC and hippocampal region that are involved in the retrieval of fear memories.